Agrobiodiversity Management for Food Security, A Critical Review - Lenné, J.M (CABI, 2014)
Biodiversity refers to all living things and the interactions between them: a vast array of organisms with an almost inﬁ nite complexity of relationships. Agricultural biodiversity, that is, ‘agrobiodiversity’, is an exceptionally important subset of biodiversity. Agrobio- diversity has been deﬁ ned by Qualset et al. (1995) as including all crops and livestock and their wild relatives, and all interacting species of pollinators, symbionts, pests, para- sites, predators and competitors. This deﬁ n- ition formed the foundation for our ﬁ rst book Agrobiodiversity: Characterization, Utilization and Management (Wood and Lenné, 1999) and remains an important basis for this second book, Agrobiodiversity Management for Food Security: a Critical Review. Agrobiodiversity through agriculture, that is, the management of the interactions between crops and domestic animals and their associated biodiversity and the environ- ment, provides most of our food with less than 5% coming from the wild (Prescot -Allen and Prescot -Allen, 1986 [for the USA]; Wood and Lenné, 1999). Most of our food is also derived directly or indirectly from plants. It has been estimated that more than 80% of our calories and edible dry weight comes from crop plants (Evans, 2003).